GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

GFF Political Economy of Health System Reforms
This webinar provided the unique opportunity to hear from and exchange with Dr. Muhammad Pate, (Director of the Global Financing Facility and Global Director of the Health, Nutrition and Population Global Practice of the World Bank) on the political economy of health system reforms and, particularly, on the transformative approach of the GFF. Summary Note Video
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); development partners / parceiros de cooperação; health / saúde